2014
DOI: 10.5455/medarh.2014.68.124-127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Rehabilitation After Cerebrovascular Accident in Patients with Diabetes Mellitus and Hypertension as Risk Factors

Abstract: Aim:The aim of this study is to evaluate the results of rehabilitation, to determine the prevalence of major risk factors in cerebrovascular accident and their consequences, as well as to propose measures and procedures that will affect the better rehabilitation.Methods:The survey analyzed: age, sex, duration of rehabilitation, activities in daily life through the Barthel index at admission and at discharge, presence of risk factors HTA and DM. The study included a total of 116 patients, the majority of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Although the underlying mechanism between diabetes mellitus and dementia is still unclear, it is suggested that diabetes mellitus is a major risk factor for cerebrovascular disease, a disorder that significantly increases the dementia risk (Sasaki et al, 1995;Hennessey and Westrick, 1998;Tanovic et al, 2014). Recent studies further indicated that diabetes is a risk factor for cerebrovascular disease, such as stroke and hypertension, and both diabetes and cerebrovascular are predictors of dementia, this suggests that the association between diabetes mellitus and dementia is likely to be mediated through cerebrovascular disease (Rossi et al, 2006;Tseng, 2006;Banerjee et al, 2012;Khoury et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanism between diabetes mellitus and dementia is still unclear, it is suggested that diabetes mellitus is a major risk factor for cerebrovascular disease, a disorder that significantly increases the dementia risk (Sasaki et al, 1995;Hennessey and Westrick, 1998;Tanovic et al, 2014). Recent studies further indicated that diabetes is a risk factor for cerebrovascular disease, such as stroke and hypertension, and both diabetes and cerebrovascular are predictors of dementia, this suggests that the association between diabetes mellitus and dementia is likely to be mediated through cerebrovascular disease (Rossi et al, 2006;Tseng, 2006;Banerjee et al, 2012;Khoury et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quanto ao enfoque temático, pode-se observar em todos os artigos selecionados que as ações necessárias na reabilitação do paciente com AVE devem levar em consideração fatores sociais, condições pré-morbidas além de funções pós-AVE, indispensáveis na tomada de decisão para realizar a reabilitação 24 . É importante considerar ações direcionadas nos fatores de risco para HAS e DM por meio da prevenção primária e secundária, e educação do paciente sobre a detecção e tratamento precoce desses fatores de risco 21 .…”
Section: Discussionunclassified
“…They found that hypertensive patients who were on antihypertensive treatment prior to their stroke had better functional outcomes (modified Rankin Scale) post stroke compared to those who were not on treatment. Tanovic et al 22 evaluated the influence of hypertension on stroke patients, and found that those with hypertension had significantly poorer outcomes on the Barthel Index than those without.…”
Section: Introductionmentioning
confidence: 99%